Sensitive quantification of Clostridium perfringens in human feces by quantitative real-time PCR targeting alpha-toxin and enterotoxin genes - Nagpal, Ravinder; Ogata, Kiyohito; Tsuji, Hirokazu; Matsuda, Kazunori; Takahashi, Takuya; Nomoto, Koji; Suzuki, Yoshio; Kawashima, Kazunari; Nagata, Satoru; Yamashiro, Yuichiro (BMC microbiology, 2015)
Clostridium perfringens is a widespread pathogen, but the precise quantification of this subdominant gut microbe remains difficult due to its low fecal count (particularly in asymptomatic subjects) and also due to the presence of abundant polymerase-inhibitory substances in human feces. Also, information on the intestinal carriage of toxigenic C. perfringens strains in healthy subjects is sparse. Therefore, we developed a sensitive quantitative real-time PCR assays for quantification of C. perfringens in human feces by targeting its α-toxin and enterotoxin genes. To validate the assays, we finally observed the occurrence of α-toxigenic and enterotoxigenic C. perfringens in the fecal microbiota of healthy Japanese infants and young adults. The plc-specific qPCR assay was newly validated, while primers for 16S rRNA and cpe genes were retrieved from literature. The assays were validated for specificity and sensitivity in pre-inoculated fecal samples, and were finally applied to quantify C. perfringens in stool samples from apparently healthy infants (n 124) and young adults (n 221). The qPCR assays were highly specific and sensitive, with a minimum detection limit of 10(3) bacterial cells/g feces. Alpha-toxigenic C. perfringens was detected in 36% infants and 33% adults, with counts ranging widely (10(3)-10(7) bacterial cells/g). Intriguingly, the mean count of α-toxigenic C. perfringens was significantly higher in infants (6.0±1.5 log10 bacterial cells/g), as compared to that in adults (4.8±1.2). Moreover, the prevalence of enterotoxigenic C. perfringens was also found to be significantly higher in infants, as compared to that in adults. The mean enterotoxigenic C. perfringens count was 5.9±1.9 and 4.8±0.8 log10 bacterial cells/g in infants and adults, respectively. These data indicate that some healthy infants and young adults carry α-toxigenic and enterotoxigenic C. perfringens at significant levels, and may be predisposed to related diseases. Thus, high fecal carriage of toxigenic C. perfringens in healthy children warrants further investigation on its potential sources and clinical significance in these subjects. In summary, we present a novel qPCR assay for sensitive and accurate quantification of α-toxigenic and enterotoxigenic C. perfringens in human feces, which should facilitate prospective studies of the gut microbiota.